Pelatihan Desain Media Pembelajaran Tata Surya untuk Meningkatkan Kreativitas Mahasiswa Sains - Jasdar Agus; Zuhrah Adminira; Munawwarah Munawwarah; Sitti Faika (Paramacitra Jurnal Pengabdian Masyarakat, 2026)
The development of information technology demands innovation in the visualization of abstract scientific concepts, such as the solar system, which are often difficult to understand through traditional media. This Community Service activity aims to provide training in learning media design to enhance the creativity and technical skills of science students in producing innovative learning media. The method used is a structured workshop-based training approach and practical mentoring, covering the preparation, implementation, and evaluation phases. Participants are guided in designing storyboards and applying media principles. Evaluation of the training's effectiveness is carried out through product assessments by a team of experts and a creativity questionnaire to assess changes in participants' mindsets. The results of the activity showed that students successfully produced various creative works, such as 3D pop-up planet models, visualizations of the layers of the sun, eclipse simulations, and constellations with scientific accuracy. The expert team's assessment confirmed that the students' products met learning media quality standards in terms of scientific accuracy, multimedia principles, and visual appeal. Furthermore, the questionnaire results showed significant improvements in students' ability to explore ideas, solve technical problems, and gain confidence in using digital technology. This process has been shown to increase participants' cognitive engagement and information retention in complex science material. Overall, this training is effective in developing science students' innovative and skilled capacities in 21st-century literacy.